ENGLISH EDUCATION STUDENTS’ PERCEPTIONS OF CHATGPT AI IN ENGLISH LEARNING TOOL - Hertiki - Hertiki; Farah Alifiah; Razanawati Nordin (Widya Mandala Surabaya Catholic University, 2025)
This research explored English education students' perceptions of ChatGPT AI as an English learning tool at Universitas PGRI Adi Buana Surabaya. As AI becomes more relevant in education, understanding students' experiences and challenges is increasingly important. The research employed a qualitative descriptive method, using open-ended questions interviews to gather insights from five participants. Findings revealed notable benefits, such as time efficiency, enhanced grammar and vocabulary knowledge, increased productivity, promotion of independent learning, and adaptability to diverse learning needs. However, challenges like over-reliance, overly general responses, technical disruptions, the necessity for specific prompts, and limitations in providing credible academic sources were also identified. The research underscored ChatGPT's potential as a supplementary tool that supported language learning while highlighting the importance of human guidance in maintaining educational balance.